DEVELOPMENT OF FUZZY MODEL IN AQUA JET PEENING ON AL 6063-T6 ALLOY D.S.Balaji*1, T.Jeyapoovan2 Department of Mechanical Engineering Hindustan Institute of Technology and Science, Chennai, India *Corresponding author E-mail: balajimailer@gmail.com Abstr - D.S.Balaji, T.Jeyapoovan; D.S.Balaji, T.Jeyapoovan (International Journal of Advanced Science and Technology, 2020)
Aqua jet peening (AJP) is a novel surface strengthening process used to enhance the properties of the material. In this paper, a fuzzy model has been generated for the experiments conducted by using Box Behnken experimental design. The input factors considered in this work are Aqua jet pressure, Standoff length, traverse rate.. The response factors such as microhardness, surface roughness, and compressive residual stress were considered to compare the peening performance numerically. The results from the Fuzzy interface system are compared with experimental results, and minor deviations were reported. Keywords: Aqua jet peening, fuzzy logic, hardness, surface roughness